Cosmic Ray phenomena during the novembre 1960 solar disturbances - Roederer, Juan; Manzano, J. R.; Santoche, O. R.; Nerurkar, N.; Troncoso, O.; Palmeira, R. A. R.; Schwachheim, G. (American Geophysical Union, 1961)
Fil: Roederer, Juan Comisión Nacional de Energía Atómica; Argentina